Curable resin compositions, cured products, and electronic components

JP2026166286APending Publication Date: 2026-10-14TAIYO HOLDINGS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025059142
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0023】 本発明の一態様によれば、めっき層との密着性が良好な硬化物を形成し得る硬化性樹脂組成物を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166286000001
    Figure 2026166286000001
  • Figure 2026166286000002
    Figure 2026166286000002
  • Figure 2026166286000003
    Figure 2026166286000003
Patent Text Reader

Abstract

To provide a curable resin composition that can form a cured product with good adhesion to the plating layer. [Solution] A curable resin composition comprising a thermosetting resin, a curing agent, and a composite metal oxide, wherein the composite metal oxide is a copper-iron-manganese composite metal oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a curable resin composition, a cured product, and an electronic component.

Background Art

[0002] With the miniaturization and multi-functionalization of electronic devices such as mobile phones and copiers, there is a demand for compactly accommodating circuit boards on the inner and outer surfaces of housings. Three-dimensional circuit boards are those in which conductive wirings are formed three-dimensionally instead of planarly on housings or electronic components, and are excellent in terms of space efficiency, improved design, and reduction in the number of components through integration of components and circuits. There are a wide variety of methods for manufacturing three-dimensional circuit boards, and methods such as mounting by bending flexible circuit boards have been used, but these methods are labor-intensive and costly, and there is a limit to further increase in density. Accordingly, methods have been proposed for forming circuits directly on a molded three-dimensional substrate.

[0003] As one method for manufacturing three-dimensional circuit boards, the LDS (Laser Direct Structuring) method is known, in which metal nuclei are generated by irradiating a molded body formed from a molding material in which a non-conductive metal complex is dispersed with a laser beam, and then plating is performed to form a circuit on the three-dimensional substrate. For example, Patent Document 1 describes a method of processing a non-conductive substrate material containing a non-conductive metal compound into a structural member, releasing heavy metal nuclei by laser electromagnetic radiation, and then chemically reducing and metallizing the structural member, thereby forming a circuit on a three-dimensional substrate.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Summary of Invention

Problems to be Solved by the Invention

[0005] However, in the case of three-dimensional circuit boards manufactured using the LDS method, the adhesion strength of the plating layer formed on the molded body may not be sufficient.

[0006] Therefore, one aspect of the present invention aims to provide a curable resin composition that can form a cured product with good adhesion to a plating layer. [Means for solving the problem]

[0007] The present invention encompasses the following aspects.

[0008] [1] comprising a thermosetting resin, a curing agent and a composite metal oxide, A curable resin composition in which the composite metal oxide is a copper-iron-manganese composite metal oxide.

[0009] [2] The curable resin composition according to [1], wherein the composite metal oxide has a composition in which the ratio of the number of moles of copper to the total number of moles of copper, iron, and manganese is 0.20 or more and 0.80 or less.

[0010] [3] The curable resin composition according to [1] or [2], wherein the composite metal oxide has a composition in which the ratio of the number of moles of iron to the total number of moles of copper, iron and manganese is 0.10 or more and 0.60 or less.

[0011] [4] The curable resin composition according to any one of [1] to [3], wherein the composite metal oxide has a composition in which the ratio of the number of moles of manganese to the total number of moles of copper, iron, and manganese is 0.10 or more and 0.60 or less.

[0012] [5] The curable resin composition according to any one of [1] to [4], wherein the composite metal oxide has a composition in which the ratio of the total number of moles of copper and iron to the number of moles of manganese is 0.65 or more and 9.00 or less.

[0013] [6] The curable resin composition according to any one of [1] to [5], wherein the composite metal oxide has a composition in which the mole fractions of copper, iron, and manganese are expressed as x, y, and 1-xy, with x being 0.20 or more and 0.80 or less, and y being 0.10 or more and 0.60 or less.

[0014] [7] The curable resin composition according to any one of [1] to [6], wherein the composite metal oxide has a volume average particle size of 0.01 μm or more and 25 μm or less.

[0015] [8] The curable resin composition according to any one of [1] to [7], wherein the content of the composite metal oxide is 1% by mass or more and 30% by mass or less on a solid content basis relative to the entire curable resin composition.

[0016] [9] A curable resin composition according to any one of [1] to [8], further comprising a solvent.

[0017]

[10] The curable resin composition according to [9], wherein the content of the solvent is 1 part by mass or more and 300 parts by mass or less per 100 parts by mass of the solid content of the curable resin composition.

[0018]

[11] A curable resin composition according to any one of [1] to

[10] , further comprising an inorganic filler.

[0019]

[12] The curable resin composition according to

[11] , wherein the content of the inorganic filler is 1% by mass or more and 70% by mass or less of the total curable resin composition in terms of solid content.

[0020]

[13] A curable resin composition according to any one of [1] to

[12] , used as an insulating material.

[0021]

[14] A cured product of any of the curable resin compositions described in [1] to

[13] .

[0022]

[15] Molded body and, The cured product described in

[14] formed on the surface of the molded body, The plating layer formed on the cured product and An electronic component comprising the same. [Effects of the Invention]

[0023] According to one aspect of the present invention, it is possible to provide a curable resin composition capable of forming a cured product with good adhesion to a plating layer. [Modes for Carrying Out the Invention]

[0024] In the present specification, the content of each component in the composition means the total amount of the plurality of substances present in the composition when a plurality of substances corresponding to each component are present in the composition, unless otherwise specified. Further, the upper and lower limits of the numerical ranges described in the present specification can be arbitrarily selected and combined from the numerical values exemplified as the numerical ranges. In the present specification, the solid content means the residue obtained by removing volatile components (for example, solvent) from the composition or its components. The acrylic resin is a general term for acrylic resins, methacrylic resins, and mixtures thereof. Hereinafter, embodiments of the present invention will be described in detail. However, the embodiments shown below are illustrative of curable resin compositions, cured products and electronic components for embodying the technical idea of the present invention, and the present invention is not limited to the curable resin compositions, cured products and electronic components shown below.

[0025] [Curable Resin Composition] The curable resin composition may contain a thermosetting resin, a curing agent, and a composite metal oxide. Further, the composite metal oxide contained in the curable resin composition may be a copper-iron-manganese based composite metal oxide.

[0026] When a laser beam is irradiated onto a cured product of a curable resin composition containing a copper-iron-manganese composite metal oxide (Cu-Fe-Mn composite metal oxide), metal nuclei of copper, iron, and manganese are formed on the surface of the cured product. Since copper and iron have higher adhesion to plating (e.g., copper plating) compared to other metals, it is thought that the adhesion of the plating layer formed when plating is applied to the cured product will be improved. For this reason, it is thought that a curable resin composition containing a copper-iron-manganese composite metal oxide can improve the adhesion to the plating layer when a plating layer is formed on the surface of the cured product of the curable resin composition. Furthermore, because the composite metal oxide contains manganese, which is black, it is thought that the thermal energy generated during laser irradiation can be efficiently absorbed, and an advantage can be obtained in that more metal nuclei can be generated.

[0027] <Thermosetting resin> The curable resin composition may contain a thermosetting resin. By including a thermosetting resin in the curable resin composition, the heat resistance and electrical insulation properties of the curable resin composition can be improved.

[0028] Examples of thermosetting resins include epoxy resins, melamine resins, phenolic resins, urea resins, unsaturated polyester resins, thermosetting acrylic resins, diallyl phthalate resins, and maleimide resins. These may be used individually or in combination of two or more types.

[0029] From the viewpoint of heat resistance, the thermosetting resin preferably contains at least one selected from the group consisting of epoxy resins and phenolic resins, more preferably contains at least an epoxy resin, and even more preferably contains both an epoxy resin and a phenolic resin.

[0030] Examples of epoxy resins include bisphenol type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol E type epoxy resin, brominated bisphenol A type epoxy resin, and bisphenol S type epoxy resin, as well as their hydrogenated epoxy resins, phenol novolac type epoxy resin, cresol novolac type epoxy resin, bisphenol A novolac type epoxy resin, biphenyl type epoxy resin, naphthol type epoxy resin, naphthalene type epoxy resin, dicyclopentadiene type epoxy resin, triphenylmethane type epoxy resin, alicyclic epoxy resin, aliphatic chain epoxy resin, phosphorus-containing epoxy resin, anthracene type epoxy resin, norbornene type epoxy resin, adamantane type epoxy resin, fluorene type epoxy resin, aminophenol type epoxy resin, aminocresol type epoxy resin, alkylphenol type epoxy resin, and 1,3,5-tris(2,3-epoxypropyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione. These epoxy resins may be used individually or in combination of two or more types.

[0031] Examples of commercially available epoxy resins include jER 828, 806, 807, YX4000, YX8000, YX8034, 834 from Mitsubishi Chemical Corporation; YD-128, YDF-170, YDF-2001CA75, ZX-1059, ST-3000 from Nippon Steel Chemical & Material Corporation; EPICLON 830, 835, 840, 850, N-730A, N-695, N-870, HP7200L from DIC Corporation; TEPIC-HP from Nissan Chemical Corporation; and RE-306, NC-3000H from Nippon Kayaku Co., Ltd.

[0032] From the viewpoint of plating adhesion, the epoxy resin preferably contains at least one selected from the group consisting of bisphenol A type epoxy resin, biphenyl type epoxy resin, and dicyclopentadiene type epoxy resin.

[0033] The epoxy equivalent of the epoxy resin may be, for example, 80 g / eq or more and 2000 g / eq or less, preferably 90 g / eq or more and 1000 g / eq or less, and more preferably 100 g / eq or more and 600 g / eq or less.

[0034] The thermosetting resin preferably contains a phenolic resin in addition to the epoxy resin. The inclusion of both epoxy and phenolic resins in the thermosetting resin tends to improve its heat resistance.

[0035] Examples of phenols that constitute the phenol resin include phenol, o-cresol, p-cresol, bisphenol A, bisphenol F, bisphenol S, bisphenol, and naphthalenediol. The phenol resin may be a phenol novolac resin, which is a polycondensate of phenols and aldehydes. The hydroxyl group equivalent of the phenol resin may be, for example, 75 g / eq or more and 250 g / eq or less, preferably 100 g / eq or more and 230 g / eq or less. These are some examples.

[0036] Examples of phenolic resins include PHENOLITE TD-2131, TD-2106, TD-2093Y, TD-2090, VH-4170, KH-6021, KA-1160, KA-1163, KA-1165, LA-7054, LA-7751, LA-1356 from DIC Corporation; KAYHARD GPH-65, GPH-103, KTG-105 from Nippon Kayaku Co., Ltd.; Resitopp GRA, HB, ELPC75, ELP83H, TPM from Gun-ei Chemical Industry Co., Ltd.; and HF-1M, HF-3M, HF-4M, H-4, DL-92, MEH-7800, MEH-7851, MEH-7500 from UBE Corporation.

[0037] The content of thermosetting resin in the curable resin composition may be, on a solid content basis, for example, 18% to 98% by mass of the total curable resin composition, preferably 20% to 95% by mass, more preferably 23% to 93% by mass, and even more preferably 25% to 90% by mass. When the content of thermosetting resin is within the above range, adhesion to the plating layer can be improved.

[0038] When the thermosetting resin contains both epoxy resin and phenolic resin, the ratio of moles of phenolic hydroxyl groups in the phenolic resin to moles of epoxy groups in the epoxy resin (phenolic hydroxyl groups / epoxy groups) may be, for example, 0.1 to 2.0, preferably 0.2 to 1.8, more preferably 0.3 to 1.7, and even more preferably 0.4 to 1.6. When the ratio of moles of phenolic hydroxyl groups to epoxy groups is within the above range, heat resistance tends to be improved.

[0039] <Hardening agent> The curable resin composition may contain a curing agent. The curing agent may be a thermosetting catalyst for a thermosetting resin.

[0040] Examples of curing agents include imidazole derivatives such as imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 4-phenylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-(2-cyanoethyl)-2-ethyl-4-methylimidazole, and 2-phenyl-4,5-dihydroxymethylimidazole; and amine compounds such as dicyandiamide, benzyldimethylamine, 4-(dimethylamino)-N,N-dimethylbenzylamine, 4-methoxy-N,N-dimethylbenzylamine, and 4-methyl-N,N-dimethylbenzylamine. Examples of substances include: hydrazine compounds such as adipic acid dihydrazide and sebacate dihydrazide; phosphorus compounds such as triphenylphosphine; and s-triazine derivatives such as guanamine, acetoguanamine, benzoguanamine, melamine, 2,4-diamino-6-methacryloyloxyethyl-s-triazine, 2-vinyl-2,4-diamino-s-triazine, 2,4-diamino-6-(2'-methylimidazolyl)ethyl-1,3,5-triazine, 2-vinyl-4,6-diamino-S-triazine isocyanuric acid adduct, and 2,4-diamino-6-methacryloyloxyethyl-s-triazine isocyanuric acid adduct. Examples of commercially available products include 2MZ-A, 2MZ-OK, 2PHZ, 2P4BHZ, 2P4MHZ, 2PHZ-PW, and 2MZA-PW (all trade names for imidazole compounds) from Shikoku Chemicals, Inc., and U-CAT(registered trademark) 3503N and U-CAT3502T (both trade names for dimethylamine blocked isocyanate compounds), DBU, DBN, U-CATSA102, and U-CAT5002 (all bicyclic amidine compounds and their salts) from Sunapro Co., Ltd. The curing agent may be used alone or in combination of two or more types.

[0041] The curing agent content may be, for example, 0.1% to 20% by mass, preferably 0.3% to 15% by mass, and more preferably 0.5% to 10% by mass, based on solid content relative to the total amount of curable resin composition.

[0042] When the thermosetting resin contains an epoxy resin, the curing agent content in the curable resin composition may be, for example, 0.5 parts by mass or more and 25 parts by mass or less, preferably 0.8 parts by mass or more and 20 parts by mass or less, and more preferably 1 part by mass or more and 15 parts by mass or less, per 100 parts by mass of solids of the epoxy resin.

[0043] <Composite metal oxides> The curable resin composition may contain a composite metal oxide. By including a composite metal oxide, the curable resin composition can be applied to the LDS method. Preferably, the composite metal oxide contains a copper-iron-manganese composite metal oxide. By including a copper-iron-manganese composite metal oxide, a cured product with good plating deposition properties and adhesion to the plating layer can be formed.

[0044] The composite metal oxide preferably has a composition in which the ratio of moles of copper to the total number of moles of copper, iron, and manganese, Cu / (Cu+Fe+Mn), is 0.20 or more and 0.80 or less. When the molar ratio Cu / (Cu+Fe+Mn) is above the lower limit, adhesion to the plating layer tends to improve. Also, when the molar ratio Cu / (Cu+Fe+Mn) is below the upper limit, electrical insulation tends to improve. The molar ratio Cu / (Cu+Fe+Mn) may more preferably be 0.22 or more and 0.78 or less, even more preferably 0.25 or more and 0.75 or less, and particularly preferably 0.30 or more and 0.70 or less.

[0045] The composite metal oxide preferably has a composition in which the ratio of the number of moles of iron to the total number of moles of copper, iron, and manganese, Fe / (Cu+Fe+Mn), is 0.10 or more and 0.60 or less. When the molar ratio Fe / (Cu+Fe+Mn) is above the lower limit, adhesion to the plating layer tends to improve. Also, when the molar ratio Fe / (Cu+Fe+Mn) is below the upper limit, electrical insulation tends to improve. The molar ratio Fe / (Cu+Fe+Mn) may more preferably be 0.12 or more and 0.57 or less, even more preferably 0.15 or more and 0.55 or less, and particularly preferably 0.20 or more and 0.50 or less.

[0046] The composite metal oxide preferably has a composition in which the ratio of moles of manganese to the total number of moles of copper, iron, and manganese, Mn / (Cu+Fe+Mn), is 0.10 or more and 0.60 or less. When the molar ratio Mn / (Cu+Fe+Mn) is above the lower limit, the plating deposition properties tend to improve further. Also, when the molar ratio Mn / (Cu+Fe+Mn) is below the upper limit, the adhesion to the plating layer tends to improve further. The molar ratio Mn / (Cu+Fe+Mn) may more preferably be 0.12 or more and 0.57 or less, even more preferably 0.15 or more and 0.55 or less, and particularly preferably 0.20 or more and 0.50 or less.

[0047] Copper and iron have better adhesion to plating (e.g., copper plating) compared to manganese. Therefore, from the viewpoint of further improving adhesion to the plating layer, it is preferable that the composite metal oxide has a composition with a high content of copper and iron.

[0048] From the viewpoint of adhesion to the plating layer, the composite metal oxide preferably has a composition in which the ratio of the total number of moles of copper and iron to the number of moles of manganese (Cu+Fe) / Mn is 0.65 or higher. The molar ratio (Cu+Fe) / Mn may preferably be 0.65 or more and 9.00 or less, more preferably 0.70 or more and 8.00 or less, even more preferably 0.85 or more and 7.00 or less, and particularly preferably 1.00 or more and 6.00 or less.

[0049] From the viewpoint of adhesion to the plating layer, the composite metal oxide is composed of copper, iron, and manganese in a total number of moles. It is preferable that the composition has a molar ratio (Cu+Fe) / (Cu+Fe+Mn) of 0.40 or higher for the total number of moles of copper and iron. The molar ratio (Cu+Fe) / (Cu+Fe+Mn) may preferably be 0.45 or more and 0.90 or less, more preferably 0.50 or more and 0.85 or less, and even more preferably 0.55 or more and 0.80 or less.

[0050] The composite metal oxide preferably has a composition in which the mole fractions of copper, iron, and manganese are expressed as x, y, and 1-xy, with x being 0.20 or more and 0.80 or less, and y being 0.10 or more and 0.60 or less; more preferably, with x being 0.25 or more and 0.75 or less, and y being 0.15 or more and 0.55 or less; and even more preferably, with x being 0.30 or more and 0.70 or less, and y being 0.20 or more and 0.50 or less. Furthermore, the composite metal oxide may have a composition in which the number of moles of oxygen per total mole of copper, iron, and manganese is, for example, 1 to 3 moles.

[0051] The composition of copper, iron, and manganese in a composite metal oxide can be adjusted by controlling the ratio of each metal-containing raw material in the raw material mixture of the composite metal oxide.

[0052] The volume-average particle size of the composite metal oxide may be, for example, 0.01 μm or more and 25 μm or less. If the volume-average particle size of the composite metal oxide is below the above upper limit, adhesion to the plating layer may be further improved. Also, if the volume-average particle size of the composite metal oxide is above the above lower limit, the plating deposition performance tends to be further improved. The volume-average particle size of the composite metal oxide may preferably be 0.1 μm or more and 20 μm or less, more preferably 0.3 μm or more and 15 μm or less, even more preferably 0.5 μm or more and 10 μm or less, even more preferably 0.8 μm or more and 5 μm or less, and particularly preferably 1 μm or more and 3 μm or less.

[0053] The volume-average particle size of a composite metal oxide is the volume-average particle size (D50) that includes not only the particle size of the primary particles but also the particle size of the secondary particles (aggregates), and is the D50 value measured by laser diffraction. The volume-average particle size (D50) is the particle size corresponding to the cumulative 50% from the smallest diameter side, measured using a laser diffraction particle size distribution analyzer to determine the cumulative particle size distribution based on volume. An example of a laser diffraction measuring device is the MicrotracMT33 00EXII manufactured by Microtrac-Bell Corporation. Furthermore, the volume-average particle size of a composite metal oxide contained in a curable resin composition refers to the value measured as described above for the composite metal oxide before the curable resin composition is prepared (pre-mixed, kneaded).

[0054] The curable resin composition may further contain a second composite metal oxide other than the copper-iron-manganese composite metal oxide (first composite metal oxide) in addition to the copper-iron-manganese composite metal oxide. Examples of the second composite metal oxide include copper-chromium composite metal oxide, antimony-tin composite metal oxide, phosphorus-tin composite metal oxide, and zinc-aluminum composite metal oxide.

[0055] When the curable resin composition contains a first composite oxide and a second composite metal oxide, the content of the first composite metal oxide is preferably 80% by mass or more and 100% by mass or less, more preferably 90% by mass or more and 100% by mass or less, even more preferably 95% by mass or more and 100% by mass or less, and particularly preferably 98% by mass or more and 100% by mass or less, based on the total amount of the first composite oxide and the second composite metal oxide, from the viewpoint of adhesion to the plating layer, and the content of the first composite metal oxide may be substantially 100% by mass. From the viewpoint of environmental considerations, it is preferable that neither the first composite oxide nor the second composite metal oxide contains chromium.

[0056] The content of composite metal oxides in the curable resin composition may be, on a solid content basis, for example, 1% to 30% by mass of the total curable resin composition, preferably 3% to 28% by mass, more preferably 4% to 25% by mass, and even more preferably 5% to 20% by mass. When the content of composite metal oxides is above the lower limit, plating deposition properties and plating adhesion tend to improve, and when it is below the upper limit, electrical insulation properties tend to improve.

[0057] The mass ratio of the content of composite metal oxide to the content of thermosetting resin in the curable resin composition (composite metal oxide / thermosetting resin) may be, for example, 0.01 or more and 1 or less on a solid content basis, preferably 0.03 or more and 0.8 or less, more preferably 0.04 or more and 0.5 or less, even more preferably 0.05 or more and 0.3 or less, and particularly preferably 0.08 or more and 0.28 or less. When the mass ratio is within the above range, the plating deposition properties and plating adhesion tend to be further improved.

[0058] When the thermosetting resin includes an epoxy resin, the content of the composite metal oxide in the curable resin composition may be, for example, 1 to 60 parts by mass, preferably 5 to 50 parts by mass, more preferably 7 to 40 parts by mass, and even more preferably 10 to 35 parts by mass, per 100 parts by mass of the solid content of the epoxy resin.

[0059] The method for preparing the composite metal oxide is not particularly limited. For example, it can be prepared by mixing raw materials containing copper, iron, and manganese (e.g., oxides or carbonates of copper, iron, and manganese) in a desired molar ratio of copper, iron, and manganese, and then heat-treating the resulting raw material mixture.

[0060] <Solvent> The curable resin composition may contain a solvent. The viscosity of the curable resin composition can be adjusted by including a solvent.

[0061] Examples of solvents include ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, diethylene glycol monomethyl ether acetate, and tripropylene glycol monomethyl ether; esters such as ethyl acetate, butyl acetate, butyl lactate, cellosolve acetate, butyl cellosolve acetate, carbitol acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, and propylene carbonate; aliphatic hydrocarbons such as octane and decane; and petroleum-based solvents such as petroleum ether, petroleum naphtha, and solvent naphtha. These solvents may be used individually or in combination of two or more.

[0062] If the curable resin composition contains a solvent, the solvent content may be, for example, 1 to 300 parts by mass per 100 parts by mass of the solid content of the curable resin composition, preferably 5 parts by mass or more, more preferably 10 parts by mass or more, even more preferably 15 parts by mass or more, and also preferably 250 parts by mass or less, more preferably 220 parts by mass or less, and even more preferably 200 parts by mass or less.

[0063] <Inorganic filler> The curable resin composition may contain inorganic fillers. By including inorganic fillers, the mechanical strength and heat resistance of the cured product of the curable resin composition can be improved.

[0064] Examples of inorganic fillers that can be used include silica, crystalline silica, Neuburg silica, aluminum hydroxide, glass powder, talc, clay, magnesium carbonate, calcium carbonate, natural mica, synthetic mica, aluminum hydroxide, barium sulfate, barium titanate, iron oxide, non-fibrous glass, hydrotalcite, mineral wool, aluminum silicate, calcium silicate, zinc oxide, etc. Inorganic fillers may be used individually or in combination of two or more types.

[0065] From the viewpoint of mechanical strength, the inorganic filler preferably contains at least one selected from the group consisting of silica, talc, and barium sulfate, and the silica is more preferably fumed silica.

[0066] The particle size of the inorganic filler is not particularly limited, but the inorganic filler may have a volume-average particle size of, for example, 0.10 μm to 40 μm, preferably 0.10 μm to 35 μm, more preferably 0.30 μm to 30 μm, and even more preferably 0.50 μm to 25 μm. When the volume-average particle size of the inorganic filler is below the above upper limit, surface smoothness tends to improve. Also, when the volume-average particle size of the inorganic filler is above the above lower limit, dispersibility tends to improve. The volume-average particle size of the inorganic filler is the volume-average particle size (D50) that includes not only the particle size of the primary particles but also the particle size of the secondary particles (aggregates), similar to the volume-average particle size of the composite metal oxide, and is the D50 value measured by laser diffraction. It can also be measured in the same way as the volume-average particle size of the composite metal oxide.

[0067] The inorganic filler content in the curable resin composition may be, on a solid content basis, for example, 1% by mass or more and 70% by mass or less, preferably 1.5% by mass or more and 67% by mass or less, more preferably 2% by mass or more and 65% by mass or less, and even more preferably 2.5% by mass or more and 63% by mass or less, relative to the total curable resin composition.

[0068] The mass ratio of the inorganic filler content to the thermosetting resin content in the curable resin composition (inorganic filler / thermosetting resin) may be preferably 0.01 or more and 3 or less, more preferably 0.02 or more and 2.5 or less, and even more preferably 0.03 or more and 2.2 or less, in terms of solid content.

[0069] When the thermosetting resin contains an epoxy resin, the amount of inorganic filler in the curable resin composition may be, for example, 1 to 400 parts by mass, preferably 2 to 350 parts by mass, more preferably 3 to 330 parts by mass, and even more preferably 5 to 310 parts by mass, per 100 parts by mass of solids of the epoxy resin.

[0070] <Thermoplastic resin> In one embodiment, the curable resin composition may contain a thermoplastic resin. The inclusion of a thermoplastic resin in the curable resin composition makes it suitable for use as a three-dimensional substrate material as described later. When the curable resin composition is used as a coating material as described later, the curable resin may or may not contain a thermoplastic resin.

[0071] Examples of thermoplastic resins include polyethylene, polypropylene, polystyrene, ABS resin, vinyl chloride resin, methyl methacrylate resin, nylon, polyester resin, fluororesin, polycarbonate polyacetal, polyamide, polyphenylene ether, amorphous polyarylate, polysulfone, polyethersulfone, polyphenylene sulfide, polyetheretherketone, polyimide, polyetherimide, and liquid crystal polymers.

[0072] When the curable resin composition contains a thermoplastic resin, the content of the thermoplastic resin in the curable resin composition may be, for example, 0.01% by mass or more and 30% by mass or less, preferably 20% by mass or less, and more preferably 10% by mass or less, based on the solid content of the entire curable resin composition.

[0073] <Additives> The curable resin composition may contain additives that are known and commonly used in the field of electronic materials. Other additives include, for example, colorants, ultraviolet absorbers, silane coupling agents, plasticizers, flame retardants, antistatic agents, anti-aging agents, antibacterial and antifungal agents, defoaming agents, leveling agents, thickeners, adhesion promoters, thixotropic agents, organic fillers, mold release agents, surface treatment agents, dispersants, dispersion aids, surface modifiers, stabilizers, phosphors, and the like.

[0074] The additive content in the curable resin composition may be, on a solid content basis, for example, 0.01% by mass or more and 10% by mass or less, preferably 0.1% by mass or more and 7% by mass or less, and more preferably 0.1% by mass or more and 5% by mass or less, relative to the total curable resin composition.

[0075] Curable resin compositions can be produced by known methods. For example, they can be prepared by blending the components contained in a curable resin composition and stirring and kneading them using a stirrer, kneader, etc.

[0076] When a cured product of a curable resin composition according to one aspect of the present invention is irradiated with a laser beam, a metallic core is generated. Then, by plating the metallic core generated by the laser beam irradiation, a plating layer having high adhesion strength to the cured product can be formed on the cured product. The curable resin composition and its cured product can be suitably used in the LDS method for manufacturing three-dimensional circuit boards. The curable resin composition and its cured product can be suitably used as an insulating material in substrates, particularly three-dimensional circuit boards.

[0077] In one aspect of the present invention, the curable resin composition can be used, for example, in the manufacture of a three-dimensional circuit board by the LDS method, by (1) using the curable resin composition as a three-dimensional substrate material, or (2) using the curable resin composition as a coating material for the surface of the three-dimensional substrate.

[0078] When a curable resin composition is used as a three-dimensional substrate material, it is preferable that the curable resin composition contains a thermoplastic resin. On the other hand, when a curable resin composition is used as a coating material, the curable resin composition may or may not contain a thermoplastic resin.

[0079] When a curable resin composition is used as a coating material, it is preferable that the curable resin composition contains a solvent. The solvent content in the curable resin composition can be appropriately set, for example, within the range described above, depending on the preferred viscosity suitable for the coating method or application method of the curable resin composition.

[0080] The present invention may, in one embodiment, include a cured product. The cured product is obtained by curing the above-mentioned curable resin composition. The cured product can be suitably used as an insulating material in substrates such as three-dimensional circuit boards. The cured product may be a cured film with a thickness of, for example, 5 μm to 500 μm, preferably 10 μm to 400 μm, and more preferably 15 μm to 300 μm, and can be suitably used as an insulating resin layer, particularly an LDS layer.

[0081] In one embodiment, the present invention may encompass an electronic component comprising a molded body, a cured product formed on the surface of the molded body, and a plating layer formed on the cured product. Here, "electronic component" means a component used in an electronic circuit, and examples include printed circuit boards and three-dimensional circuit boards. The electronic component may be a three-dimensional circuit board.

[0082] Examples of molded products include resin molded products such as thermoplastic resin molded products and thermosetting resin molded products; metal molded products; ceramic molded products; carbon fiber molded products; wood, etc.

[0083] Since the molded body has a cured product of the curable resin composition containing a composite metal oxide on its surface, the molded body itself may not substantially contain a composite metal oxide.

[0084] The cured material formed on the surface of the molded body may have a thickness of, for example, 5 μm or more and 500 μm or less, preferably 10 μm or more and 400 μm or less, and more preferably 15 μm or more and 300 μm or less.

[0085] Cured products can be formed on the surface of a molded body by coating or applying a curable resin composition to the surface of the molded body and curing the dried coating film of the curable resin composition by heating or other means. Examples of application methods include dip coating, flow coating, roll coating, bar coating, screen printing, curtain coating, inkjet coating, dispensing, and spraying.

[0086] From the viewpoint of conductivity, copper plating is preferred. The plating layer formed on the hardened material may have a thickness of, for example, 1 μm to 50 μm, and preferably 5 μm to 35 μm. The plating layer can be formed on the hardened material formed on the surface of the molded body by irradiating the hardened material with a laser beam to generate metal nuclei, and then plating the metal nuclei generated by the laser beam. By irradiating the laser beam in accordance with the circuit pattern, a circuit can be formed on the molded body (three-dimensional substrate).

[0087] The laser beam is not particularly limited as long as it can cause the metal to be emitted when irradiated onto the composite metal oxide. Examples of laser beam wavelengths that can be used include 248 nm, 308 nm, 355 nm, 532 nm, 1064 nm, and 10600 nm.

[0088] The plating layer can be formed by applying electroplating or electroless plating, preferably electroless plating, to a metal core generated by a laser beam. [Examples]

[0089] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Unless otherwise specified, "parts" and "%" are based on mass.

[0090] [Preparation of copper-iron-manganese composite metal oxides] Copper oxide (CuO), iron oxide (Fe2O3), and manganese oxide (MnO) were mixed to achieve the desired molar ratios of copper, iron, and manganese. The mixture was then heat-treated at 700°C for 5 hours and subsequently pulverized to prepare CuFeMn-based oxide particles 1-7.

[0091] [Preparation of curable resin composition] Each component was blended in the proportions (parts by mass) shown in Tables 1 to 3, pre-mixed with a stirrer, and then dispersed using a three-roll mill to prepare the curable resin compositions for Examples 1 to 23 and Comparative Examples 1 to 2.

[0092] [Table 1]

[0093] [Table 2]

[0094] [Table 3]

[0095] The components in Tables 1 to 3 are as follows:

[0096] (thermosetting resin) *1 EPICLON HP7200L dicyclopentadiene type epoxy resin manufactured by DIC Corporation, epoxy equivalent: 272g / eq *2 EPICLON 840 Bisphenol A type epoxy resin manufactured by DIC Corporation, epoxy equivalent: 183g / eq *3 Nippon Kayaku Co., Ltd., NC-3000H biphenyl-type epoxy resin, epoxy equivalent: 288g / eq *4 HF-1M phenolic resin manufactured by UBE Corporation, hydroxyl group equivalent: 103g / eq

[0097] (Hardening agent) *5 2-phenyl-4,5-dihydroxymethylimidazole, manufactured by Shikoku Chemicals, Inc. *6 2,4-diamino-6-(2'-methylimidazolyl)ethyl-1,3,5-triazine, manufactured by Shikoku Chemicals, Inc. *7 DICY: Dicyandiamide

[0098] (Composite metal oxides) *8 CuFeMn-based oxide particles 1, D50: 1.4 μm Composition (molar ratio) Cu:Fe:Mn = 0.80:0.10:0.10 *9 CuFeMn-based oxide particles 2, D50: 1.3 μm Composition (molar ratio) Cu:Fe:Mn = 0.60:0.20:0.20 *10 CuFeMn-based oxide particles 3, D50: 1.2 μm Composition (molar ratio) Cu:Fe:Mn = 0.40:0.30:0.30 *11 CuFeMn-based oxide particles 4, D50: 1.5 μm Composition (molar ratio) Cu:Fe:Mn = 0.20:0.40:0.40 *12 CuFeMn-based oxide particles 5, D50: 1.2 μm Composition (molar ratio) Cu:Fe:Mn = 0.30:0.60:0.10 *13 CuFeMn-based oxide particles 6, D50: 1.1 μm Composition (molar ratio) Cu:Fe:Mn = 0.30:0.25:0.45 *14 CuFeMn-based oxide particles 7, D50: 1.5 μm Composition (molar ratio) Cu:Fe:Mn = 0.30:0.10:0.60 *15 Black 30C965:CuCr2O4 (Shephard color company, powder), D50:1.0μm

[0099] (Inorganic filler) *16 AEROSIL R974 Evonik Operations GmbH fumed silica *17 Adfine SO-C4 (silica filler), manufactured by Admatex Co., Ltd., D50: 1.0 μm *18 Barium sulfate, D50: 0.6 μm, manufactured by Sakai Chemical Industry Co., Ltd. *19 Manufactured by Nippon Talc Co., Ltd., talc, D50: 0.85 μm

[0100] (solvent) *20 Juxol CA, manufactured by Dow Chemical, carbitol acetate *21 Dawnol PM, manufactured by Dow Chemical Company, propylene glycol monomethyl ether

[0101] (Antifoaming agent) *22 KS-66 Silicone-based defoaming agent manufactured by Shin-Etsu Chemical Co., Ltd.

[0102] [evaluation] (Formation of hardened film 1) The curable insulating resin compositions prepared in Examples 1-7 and 9-23, and Comparative Examples 1-2, were applied to the entire surface of a polyphenylene sulfide (PPS) molded article prepared as a substrate using a dispenser to achieve a dry film thickness of 100 μm, and dried at 80°C for 30 minutes. Then, the curable resin composition was cured by heating at 150°C for 30 minutes to form a cured film on the substrate. The resulting cured film was evaluated for plating deposition properties and plating adhesion. The results are shown in Tables 1-3.

[0103] (Formation of hardened film 2) The curable resin composition prepared in Example 8 was spray-coated onto the surface of a polyphenylene sulfide (PPS) molded article prepared as a substrate, so that the film thickness after drying was 100 μm. It was then dried at 80°C for 30 minutes. Subsequently, the curable resin composition was cured by heating at 150°C for 30 minutes to form a cured film on the substrate. The plating deposition properties and plating adhesion of the obtained cured film were evaluated. The results are shown in Table 1.

[0104] <Plating deposition evaluation> An infrared laser was irradiated onto the surface of the hardened film under the following conditions. Subsequently, electroless copper plating was performed on the laser-irradiated area to deposit the plating onto the surface of the hardened film. Laser device: LPKF Fusion 3D 1200 (wavelength 1064nm) Laser conditions: Speed ​​1 m / s, output 4 W, frequency 60 kHz Plating solution: MID Copper 100XB, manufactured by MacDermid Performance Solutions Japan. Plating conditions: Immersion at 60°C for 60 minutes, Cu thickness (plating thickness): 5 μm

[0105] The plating deposition properties in the laser-irradiated area were evaluated based on the following evaluation criteria.

[0106] (Evaluation criteria for plating deposition properties) A: The plated surface is uniform and electrically conductive. B: The plated surface has some unevenness, but there are no non-conductive areas, and it is conductive. C: The plated surface is uneven and has non-conductive areas.

[0107] <Plating adhesion evaluation> Similar to the evaluation of plating deposition properties, laser irradiation and electroless copper plating were performed on the surface of the hardened film to deposit the plating. Next, 100 grid patterns of 1 mm x 1 mm were formed on the surface of the plating layer formed on the hardened film using a utility knife, and the adhesion between the plating layer and the hardened film was evaluated by peeling them off with cellophane tape (adhesion strength of 10 ± 1 N per 25 mm width). The evaluation criteria were as follows.

[0108] (Evaluation criteria for plating adhesion) A: Number of remaining board squares: 100 B: Number of remaining board squares: 80 to 99 C: Number of remaining board squares: Less than 80

[0109] As shown in Tables 1 to 3, the curable resin compositions in the examples exhibited good plating deposition properties and plating adhesion.

Claims

1. It contains a thermosetting resin, a curing agent, and a composite metal oxide. A curable resin composition in which the composite metal oxide is a copper-iron-manganese composite metal oxide.

2. The curable resin composition according to claim 1, wherein the composite metal oxide has a composition in which the ratio of the number of moles of copper to the total number of moles of copper, iron, and manganese is 0.20 or more and 0.80 or less.

3. The curable resin composition according to claim 1, wherein the composite metal oxide has a composition in which the ratio of the number of moles of iron to the total number of moles of copper, iron, and manganese is 0.10 or more and 0.60 or less.

4. The curable resin composition according to claim 1, wherein the composite metal oxide has a composition in which the ratio of the number of moles of manganese to the total number of moles of copper, iron, and manganese is 0.10 or more and 0.60 or less.

5. The curable resin composition according to claim 1, wherein the composite metal oxide has a composition in which the ratio of the total number of moles of copper and iron to the number of moles of manganese is 0.65 or more and 9.00 or less.

6. The curable resin composition according to claim 1, wherein the composite metal oxide has a composition in which the mole fractions of copper, iron, and manganese are expressed as x, y, and 1-x-y, with x being 0.20 or more and 0.80 or less, and y being 0.10 or more and 0.60 or less.

7. The curable resin composition according to claim 1, wherein the composite metal oxide has a volume-average particle size of 0.01 μm or more and 25 μm or less.

8. The curable resin composition according to claim 1, wherein the content of the composite metal oxide is 1% by mass or more and 30% by mass or less of the total curable resin composition, on a solid content basis.

9. The curable resin composition according to claim 1, further comprising a solvent.

10. The curable resin composition according to claim 9, wherein the content of the solvent is 1 part by mass or more and 300 parts by mass or less per 100 parts by mass of the solid content of the curable resin composition.

11. The curable resin composition according to claim 1, further comprising an inorganic filler.

12. The curable resin composition according to claim 11, wherein the content of the inorganic filler is 1% by mass or more and 70% by mass or less of the total curable resin composition in terms of solid content.

13. A curable resin composition according to claim 1, used as an insulating material.

14. A cured product of the curable resin composition according to any one of claims 1 to 13.

15. Molded body and, A cured product according to claim 14 is formed on the surface of the molded body, The plating layer formed on the cured product and An electronic component equipped with [the following features].

Citation Information

Patent Citations

  • Conductor track structure and method for manufacturing the same

    JP2004534408A